2016
DOI: 10.3109/09513590.2015.1126819
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on oxidative stress and apoptosis in experimental diabetes mellitus-related ovarian injury

Abstract: We aimed to evaluate the effect of melatonin on oxidative stress and ovarian injury in rats. Twenty-four Sprague-Dawley albino rats were divided into three groups: Group 1 as nondiabetic healthy controls (n = 8), group 2 as nontreated diabetic rats (n = 8) and group 3 as melatonin-treated diabetic rats (n = 8). After overt diabetes was produced by intraperitoneal injection of streptozosin, 20 mg/kg/day of melatonin was given intraperitoneally to group 3 for a week. NF-kB and caspase-3 immunoexpressions, lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 39 publications
3
22
1
1
Order By: Relevance
“…Tresguerres' group also reported that melatonin reduced age-associated increases in HOMA-IR [131]. Similar studies suggest that melatonin reduces mitochondrial dysfunction [132], inhibits oxidative enzyme activity [133], decreases apoptosis [134], improves dyslipidaemia [135] and reduces diabetes-induced oxidative stress [135]. Together, these rodent studies strengthen the assertion that reductions in melatonin promote insulin resistance and hyperglycaemia, and that these conditions can be corrected with exogenous melatonin administration.…”
Section: The Pancreatic Response To Melatoninsupporting
confidence: 69%
“…Tresguerres' group also reported that melatonin reduced age-associated increases in HOMA-IR [131]. Similar studies suggest that melatonin reduces mitochondrial dysfunction [132], inhibits oxidative enzyme activity [133], decreases apoptosis [134], improves dyslipidaemia [135] and reduces diabetes-induced oxidative stress [135]. Together, these rodent studies strengthen the assertion that reductions in melatonin promote insulin resistance and hyperglycaemia, and that these conditions can be corrected with exogenous melatonin administration.…”
Section: The Pancreatic Response To Melatoninsupporting
confidence: 69%
“…Both pathways end with the activation of caspase 3, leading to cell death [ 22 25 ]. In relation to the diabetic ovary, our results confirm previous observations that demonstrated activation of the intrinsic pathway through BAX as a consequence of hyperglycemia [ 2 , 9 , 13 18 , 26 ]. However, we observed the specific dynamics of apoptosis-related proteins, with the highest levels occurring at 15 and 20 days posttreatment in the granulose cells of antral follicles.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown an association between DM and female reproductive disturbances, including amenorrhea, early menopause onset and infertility [ 2 , 6 , 9 , 10 , 12 18 ]. These alterations have been related to the injurious effects of hyperglycemia through the overproduction of AGEs and ROS, which trigger the caspase 3 apoptosis pathway [ 2 , 4 , 6 , 13 , 16 ]. However, these studies analyzed the effects of DM at a single time point, without correlating follicular loss with the expression of apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations